Design an essential introduction - Williams, Gareth (London Goodman Fiell, an imprint of the Carlton Publishing, 2015)
"This is an indispensable, clear and concise introduction to the world of design and all its facets--a must-have for all design students and those interested in learning more about the fascinating process that turns good ideas into useful products. Design: an essential introduction invites you to delve into the creative, pragmatic and essentially optimistic world of design and introduces you to the most ingenious and inspiring designs of today." -- Provided by publisher
What is design? -- Chapter 1 What is a design brief? -- Chapter 2 What is the design process? -- Chapter 3 Form and function -- Chapter 4 Styling -- Chapter 5 Universality versus individualism -- Chapter 6 Materials and technologies -- Chapter 7 Human-centered design and ergonomics -- Chapter 8 Digital design -- Chapter 9 The impact of design -- Chapter 10 Design evolution case studies -- Chapter 11 Design and innovation -- Chapter 12 The future of design -- Why design matters
Includes bibliographical references (page 189) and index.
Keywords: Design -- Social aspects; Design and technology